2005
DOI: 10.1191/0961203305lu2242xx
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal sepsis in patients with systemic lupus erythematosus

Abstract: Severe infections by opportunistic agents and common pathogens are frequent in patients suffering from systemic lupus erythematosus (SLE) and have become one of the leading cause of death. Here we review all cases of Streptococcus pneumoniae septicaemia observed in a cohort of 208 SLE patients. Five cases were identified. We stress the severity of the clinical presentation and recommend immunization of SLE patients with a pneumococcal polysaccharide vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 24 publications
0
19
0
6
Order By: Relevance
“…In particular, recent biological treatments, such as tumour necrosis factor-alpha (TNFα) antagonists, that alter immune response are thought to increase the risk of infection 17 18. Infection has been implicated as a contributory cause of death in people with rheumatoid arthritis,19 SLE20 and inflammatory bowel diseases,21 22 and case reports have found associations between SLE23 and ulcerative colitis24 and subsequent severe pneumococcal infection. We lack information on any treatment used for immune-mediated diseases and are unable to determine the extent to which treatment may affect pneumococcal disease occurrence in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, recent biological treatments, such as tumour necrosis factor-alpha (TNFα) antagonists, that alter immune response are thought to increase the risk of infection 17 18. Infection has been implicated as a contributory cause of death in people with rheumatoid arthritis,19 SLE20 and inflammatory bowel diseases,21 22 and case reports have found associations between SLE23 and ulcerative colitis24 and subsequent severe pneumococcal infection. We lack information on any treatment used for immune-mediated diseases and are unable to determine the extent to which treatment may affect pneumococcal disease occurrence in this population.…”
Section: Discussionmentioning
confidence: 99%
“…16 Rate ratios were 2.47 for RA (95% CI 2.4-2.5), 4.2 for sclero derma (95% CI 3.8-4.7), 3.2 for Sjögren syndrome (95% CI 2.9-3.5) and 5.0 for SLE (95% CI 4.6-5.4). [17][18][19][20] Herpes zoster Prospective cohort studies of patients with RA have found a wide range in the incidence of herpes zoster (0.55-12.1 cases per 1,000 patient-years). [21][22][23][24][25][26][27][28][29] RA is a risk factor for herpes zoster (HR 1.65-1.91, compared with healthy individuals).…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%
“…S. pneumoniae is the leading cause of pneumonia in SLE patients. In SLE patients, pneumococcal pneumonia is often severe, frequently acquiring a septicemic and fulminant course, occasionally described even at disease presentation [46,47,48,49,50]. For these reasons, a polyvalent pneumococcal vaccine is strongly recommended in SLE patients [51].…”
Section: Lung Infections In Systemic Rheumatic Diseasesmentioning
confidence: 99%